Emotional Intelligence and Performance of MSME Women Enterprises (Case Study in Cangkringan District, Sleman Regency) in 2022 - Pawestri, Pebrianti; Prasetyani, Dwi (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Emotional intelligence such as self-awareness, motivation, empathy, and social skills are used to understand individual abilities in a social environment. Women in this case are considered to have a high level of emotionality compared to men, so that the success of a business and the decisions taken use more feelings. The research aims to measure the relationship between self-awareness, self-control, self-motivation, social awareness, and social skills on business performance. female entrepreneurs. The total population in this study was 248 businesses. The sampling technique in this research is Systematic Random Sampling. The sample in the study was 71 people with an interval of 3. The analysis used in this research used several PLS methods which included several analyzes including: Factor Analysis, Designing a Structural Measurement Model (Inner Model), Designing a Measurement Model (Outer Model), and Hypothesis Testing. The influence of self-awareness on the performance of MSMEs shows a coefficient value of 0.435. The effect of self-control on the performance of MSMEs shows a coefficient value of 0.054. The influence of self-motivation on the performance of MSMEs shows a coefficient value of 0.273. The influence of social awareness on the performance of MSMEs shows a coefficient value of 0.048. The influence of social skills on the performance of MSMEs shows a coefficient value of 0.246. This research shows that self-awareness has a positive and significant effect on MSME performance, and self-control has a positive and significant effect on MSME performance. Self-motivation has a positive and significant effect on MSME performance, social awareness has a positive and significant effect on MSME performance and social skills have a positive and significant effect on MSME performance.